2016
DOI: 10.18820/2519593x/pie.v34i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Pre-service teachers’ competence to teach science through information and communication technologies in South Africa

Abstract: Research suggests that there is a need for better training of prospective teachers on information and communication technologies (ICTs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Stoetzel and Shedrow (2021) found that prospective teachers lacked knowledge of technology tools and meaningful integration into their teaching. This observation was echoed by Marongwe et al (2023) and Jita (2016), who emphasised the need to adequately train aspiring teachers in the use of information and communication technologies (ICTs) for teaching and learning in schools. Without comprehensive training and understanding of ICT tools, teachers may be reluctant to adopt technology, making a case for rethinking initial teacher programs in South Africa.…”
Section: Pedagogymentioning
confidence: 99%
See 2 more Smart Citations
“…Stoetzel and Shedrow (2021) found that prospective teachers lacked knowledge of technology tools and meaningful integration into their teaching. This observation was echoed by Marongwe et al (2023) and Jita (2016), who emphasised the need to adequately train aspiring teachers in the use of information and communication technologies (ICTs) for teaching and learning in schools. Without comprehensive training and understanding of ICT tools, teachers may be reluctant to adopt technology, making a case for rethinking initial teacher programs in South Africa.…”
Section: Pedagogymentioning
confidence: 99%
“…A study conducted by Jita (2016) in South Africa revealed that preservice teachers are more familiar and comfortable with non-technology-related skills compared to technology-oriented skills. According to Jita (2016) and Marongwe et al (2023), the lack of ICT training opportunities provided to preservice teachers, as well as the failure of lecturers to incorporate ICTs in their teaching, contribute to the incompetence of initial teachers in utilising ICTs. Both studies recommend the revision of teacher education programs to include the integration of ICTs.…”
Section: Pedagogymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, appropriate ICT training programs would turn faculty members more self-efficacy in computer applications and increase their likeliness to use them for their jobs (John, 2015). Altogether, learning how to combine technology, content and pedagogy in the teaching is a pre-condition for using ICTs to teach (Jita, 2016) that in turn determines the effectiveness of online teaching environments (Hung & Chou, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This leads to failure to concentrate on programs that may be helpful in their studies and daily life application. Students need guidance on how to learn programs and search for necessary information that can contribute to their academic excellence as well as improving their skills [7]. B.…”
Section: Computer Skills Amongst Students Is Necessarymentioning
confidence: 99%